Comprehensive Review of the Role of Medical Secretaries in Health Administration and Modern Healthcare Systems Management - Makrash , Majed Ahmed; Jarh , Naseem Alhassan Ali; Hakami , Maryam Mohammed A; Almodeer , Abdulrhman Mohammed; Daeya , Ibrahim Ahmed; Bejh , Moath Adil Ali; Jafari , Lara Hussin Jaman; Khabrani, Khalid Youssef; qami , Waleed Mohammed A; Hawthan, Khaled Hassan H; Alsharari , Ahmed Awdah A; Almuammar, Hussain Musalli M (Journal of Ecohumanism, 2024)
Medical secretaries, also known as medical office assistants or healthcare administrators, ensure that healthcare organizations and the broader healthcare delivery systems are run daily. Explores the broad growing utility of medical secretaries in clinical organizations, specifically concerning patient treatment and clinical operation in healthcare organizations, more so about the applicability of information technology in healthcare facilities. In this context, the literature review intends to overview their duties and responsibilities, training, issues they face, and contributions to efficient healthcare delivery, patient satisfaction, and organizational outcomes. We can reaffirm the essentiality of medical secretaries in today's healthcare organizations and recommend measures for improving their position based on education, implementing new technologies, and professional training.